Summer at the lake - Greeley, Andrew M., 1928- (New York : Forge, 1997)
Thirty years after the tragic car wreck that killed two of their comrades, three friends--Leo Kelly, Jane Devlin, and Father "Packy" Keenan--return to the scene of their teenage idylls as they struggle to come to terms with the past, their lives, their goals, and their personal relationships.
"A Tom Doherty Associates book."
Keywords: Man-woman relationships -- Illinois -- Chicago -- Fiction; Friendship in children -- Fiction; Chicago (Ill.) -- Fiction; Love stories